Perancanaan Jembatan Beton Prategang RSUD Temanggung dengan Berbasis Building Information Modeling (BIM) 3D, 4D, dan 5D - Anandita, Dianya Puan; Nurdiana, Asri Nurdiana; Setiabudi, Bambang (Jurnal Sipil dan Arsitektur, 2023)
Building Information Modeling (BIM) technological innovations can assist in designing construction designs to be integrated with each other, so that the process can be more effective and efficient. This Building Information Modeling (BIM) technology can be applied to various construction works, including road and bridge construction work. In this study the authors will plan the construction work of a prestressed concrete bridge at Temanggung Hospital which includes bridge geometric planning, structural loading and reinforcement calculations, 3D modeling and calculation of concrete volume and reinforcement using Autodesk Revit, as well as designing a cost budget and time schedule using Microsoft Project. From the analysis. Based on the results of the analysis, obtained a 17,453-meter-long Full Circle bend plan with a 4% incline, the elevation of the bridge is 14,470 meters from the riverbed, the design of the bridge at the Temanggung Hospital is safe against work loads, the total cost needed in the construction of the Temanggung Hospital Bridge is Rp. 7,875,323,851, with a duration of work of 5 months starting from 1 August 2023 to 9 December 2023.